ANALISIS ENTREPRENEUR LIFE SKILLS MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI DI STKIP PERSADA KHATULISTIWA SINTANG - Marganingsih, Anna; Pelipa, Emilia Dewiwati; Erwin, Erwin (Jurnal Pendidikan Ekonomi (JURKAMI), 2019)
Abstract: The aims of this study is to describe the Life Skills of the Entrepreneur Life Skills of Study Program Economic Education at STKIP Persada Khatulistiwa Sintang. The method used in this research is descriptive method with quantitative approach. The population in this study were students of Economic Education Study Program at STKIP Persada KhatulistiwaÂ  Sintang totaling 133 students and the sample in this study amounted to 27 students. Data collection techniques used are indirect communication techniques. Data collection tools used were questionnaires. The data analysis technique used is descriptive statistics. The results showed that the Entrepreneurship Life Skills of Study Program Economic Education at STKIP Persada Khatulistiwa Very Good with an average questionnaire score of 4.03. Student Life Skills (Entrepreneur Life Skills) Study Program Economic Education at STKIP Persada Khatulistiwa includes Personal Life Skills is Very Good with a questionnaire score of 4.03, Social Life Skills is Very Good with a questionnaire score of 4.02, Academic Life Skills is Good with a questionnaire score of 3.7 and Vocational Skills (Vocational Life Skills) is Very Good with a questionnaire score of 4.37Keywords: Entrepreneurship, Life SkillsAbstrak: Tujuan penelitian ini adalah untuk mendeskripsikan kecakapan hidup berwirausaha (Entrepreneur Life Skills) Mahasiswa Prodi. Pendidikan Ekonomi di STKIP Persada Khatulistiwa Sintang. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah mahasiswa Prodi Pendidikan Ekonomi STKIP Persada Khatulistiwa Sintang sejumlah 133 mahasiswa dan sampel dalam penelitian berjumlah 27 Mahasiswa. Teknik Pengumpulan data yang digunakan adalah teknik komunikasi tidak langsung. Alat pengumpulan data yang digunakan adalah kuesioner. Teknik analisis data yang digunakan adalah statistik deskriptif. Hasil penelitian menunjukkan bahwa Kecakapan Hidup Berwirausaha (Entrepreneur Life Skills) Mahasiswa Prodi. Pendidikan Ekonomi di STKIP Persada Khatulistiwa Sangat Baik dengan skor rata-rata angket 4,03. Kecakapan Hidup Berwirausaha (Entrepreneur Life Skills) Mahasiswa Prodi. Pendidikan Ekonomi di STKIP Persada Khatulistiwa meliputi Kecakapan Personal (Personal Life Skill) adalah Sangat Baik dengan skor angket 4,03, Kecakapan Sosial (Social Life Skills) adalah Sangat Baik dengan skor angket 4,02, Kecakapan Akademik (Academic Life Skills) adalah Baik dengan skor angket 3,7 dan Kecakapan Vokasional (Vocational Life Skills) adalah Sangat Baik dengan skor angket 4,37Kata Kunci: Kewirausahaan, Kecakapan Hidup